Cantabria en la Alta Edad Media / Rogelio Pérez Bustamante, Javier Ortiz Real - Ortiz Real, Javier; Pérez-Bustamante, Rogelio (Historia General de Cantabria ; 3)
Tít. tomado de la cub. | Bibliografía: p.183-189Índices